From Confrontation to Reconciliation: Assessing the Strategic Implications of Saudi-Iranian Rapprochement on Gulf Security - Sobia Shabir; Noor Fatima, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Amid shifting geopolitical currents in the Middle East, analyzing changes in inter-state relations is essential for assessing prospects for regional stability. This research explores the 2023 Saudi-Iran rapprochement through the lens of Regional Security Complex Theory (RSCT), situating it within broader regional security dynamics. Long defined by sectarian, ideological and geopolitical rivalries, the Saudi-Iranian relationship has fueled proxy conflicts and deepened fragmentation across the the Middle East and North Africa (MENA) region. The recent normalization of ties, brokered by China, marks a pivotal diplomatic development, prompting critical inquiry into its underlying drivers, sustainability and broader implications for conflict resolution and alliance reconfiguration. Given the authoritarian nature of most regimes in the region, the paper focuses on the state-dominated institution, such as security mechanisms, while also examining informal power structures, including religious establishments and elite networks. Utilizing qualitative case studies of Yemen, Syria, Iraq and Lebanon, the research examines how this rapprochement is reshaping threat perceptions, patterns of proxy warfare and alliance behaviour. While preliminary signs indicate a cautious de-escalation and emerging regional pragmatism, persistent structural barriers such as mutual distrust, ideological divides and unresolved conflicts continue to challenge the durability of peace. The paper argues that this détente represents a tactical recalibration driven by strategic necessity, rather than a transformative shift in the MENA security architecture.